ONE MANAGEMENT PATTERN IN CORE-PLASMA PARTNERSHIPS: A Solution For Reducing Social Conflicts and Improving the Welfare of Oil Palm Farmers - Erdi, Erdi; Martoyo, Martoyo; Herlan, Herlan; Rupita, Rupita; Sukamto, Sukamto; Habib Padilah, Ahirul (Department of Government, FISIP, Universitas Padjadjaran, 2025)
gb777